Efektivitas Layanan Informasi Karir Dalam Meningkatkan Kemampuan Perencaanaan Karir Siswa - Djoni Aminuddin; Mulyadi Mulyadi (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2020)
This study aims to determine the effectiveness of information services in improving students' career planning skills at SMA Negeri 13 Depok. This research uses a descriptive method with a quantitative approach. The population in this study were all students of class XI in SMA Negeri 13 Depok as many as 77 students who became the study sample using purposive sampling techniques, namely how to take the subject not based on strata, random, or region but based on the existence of certain objectives. The instrument uses a Likert scale. The results showed that information services proved effective in increasing the career planning abilities of students at SMA Negeri 13 Depok. the results of the post test calculation (evaluation of results) showed that the average ability of students' career planning after being given treatment was 93.1818. Based on the results of analysis and hypothesis testing (t test) shows that there are differences in students' career planning ability before and after information services are provided. This is known from the results of the calculation of the difference between the average ability of career planning students on pre-test with the average ability of career planning on post-test of -7,15584. The implications of this study are as a reference for BK teachers that through information services have proven to be effective in improving students' career planning skills.